2022
DOI: 10.1111/apa.16596
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled nitric oxide in preterm neonates with preterm prelabour rupture of membranes, a systematic review

Abstract: Aim: To perform a systematic literature review to determine the effect of inhaled nitric oxide (iNO) on oxygenation, mortality and morbidity in preterm neonates with preterm prelabour rupture of membranes (PPROM) and early hypoxaemic respiratory failure (HRF). Methods: MEDLINE, Embase, Cochrane Central Register of Controlled Trials, Clini calTr ials.gov, Web of Science, Zetoc and ProQuest were searched. Studies including neonates <34 weeks' gestation with PPROM, oligohydramnios or pulmonary hypoplasia and HRF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…iNO is frequently used to treat neonatal hypoxic respiratory failure (persistent high pulmonary vascular pressure and resultant right-to-left shunting of blood). 6,7 We found that neonates with a longer period of MVP <1 cm more frequently used iNO after birth, whereas the period of MVP <2 cm did not affect the neonatal use of iNO.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…iNO is frequently used to treat neonatal hypoxic respiratory failure (persistent high pulmonary vascular pressure and resultant right-to-left shunting of blood). 6,7 We found that neonates with a longer period of MVP <1 cm more frequently used iNO after birth, whereas the period of MVP <2 cm did not affect the neonatal use of iNO.…”
Section: Discussionmentioning
confidence: 65%
“…Our data likewise indicate that iNO are more frequently needed in CAOS than in non‐CAOS, which suggest that exposure to bloody amniotic fluid may have increased iNO use. iNO is frequently used to treat neonatal hypoxic respiratory failure (persistent high pulmonary vascular pressure and resultant right‐to‐left shunting of blood) 6,7 . We found that neonates with a longer period of MVP <1 cm more frequently used iNO after birth, whereas the period of MVP <2 cm did not affect the neonatal use of iNO.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…A systematic review evaluating the use of iNO in premature infants with preterm premature rupture of membrane was recently published. This study concluded that iNO improved oxygenation in this population, likely secondary to the high prevalence of PPHN [ 31 ]. Two recently published studies evaluated iNO response in premature infants born at <34 weeks of gestation that was initiated for the indication of HRF associated with PPHN.…”
Section: Discussionmentioning
confidence: 99%